Social Mobilization Through Environment and Disaster Risk Management Advocacy for Climate Change Adaptation - Mani, Merian; Sespene, Jeter; Paloma, Dulce; Lucidos, Juniel (Romblon State University Research Journal, 2011)
The growing demand for environmental education is grounded on the recommendation of majority of both national and international environmental experts as the issue on climate change became a global concern. This project went a long way of conceptualization for as early as 1993 by Dr. Mani after conducting a study on the environmental status of Romblon uncovering issues such as forest denudation, degradation of coral colonies, solid waste management, pollution, and poverty. These problems have been attributed to the poor implementation of environmental laws, massive poverty, and ignorance of the people on environmental protection and preservation. The project evolved from a research study that would establish the validity and acceptability of the 6-module Instructional Materials (IM) for Environmental Education. The project used the Community In Vitro and In Vivo Development Approach in managing a resource-limited research involving multi-sectors, agencies, institutions, and stakeholders. The project’s fund grew from P500, 000.00- granted by Local Government Academy (LGA) after winning the Search for Best Project to P1.5 M counterparts of participating agencies. The project is now on Phase I with the Local Government Units and Heads of National Agencies as their partner agencies. The Phase II of the project would target to educate women and youth sectors of Romblon.